Fertilizantes com tecnologias associadas como estratégia para aumentar a eficiência da adubação nitrogenada e fosfatada - Oliveira, Yago Ricardo de (2022)
Soil fertility is one of the main factors involved in high yields, and the large losses of nitrogen (N) and the low content of phosphorus (P) available in soils have negatively impacted crop production in most regions. Thus, technological alternatives have been sought to increase the efficiency of nitrogen and phosphate fertilizers. Fertilizers with associated technologies have been produced by coating or mixing different materials, among which the use of polymers, organic acids and organic residues has been highlighted. The objective of this thesis was: (i) to evaluate corn yield and NH3 volatilization in nitrogen and phosphate fertilizers with associated technologies in different water conditions; (ii) to evaluate the productivity of conilon coffee (Coffea canephora) in response to the application of phosphate and nitrogen fertilizers with associated technologies and; (iii) to evaluate the application of nitrogen and phosphate fertilizers with associated technology in the conilon coffee crop under different water conditions. To this end, experiments were carried out under field conditions, which are presented in three chapters of the thesis. In chapter 1, the results showed that nitrogen fertilizers with associated technologies were efficient in increasing corn productivity and reducing NH3 volatilization when compared to conventional fertilizer. Technologies in nitrogen fertilizers combined with phosphate fertilizers provided increases in corn productivity and NH3 volatilization was lower in polymer coated urea (UPOL), and higher for conventional urea (UC) and urea with organic compost (UORG), for different crops and water conditions. In chapter 2, phosphate fertilizers with technologies were more efficient in increasing coffee productivity when compared to conventional MAP. The application of larger amounts of phosphate fertilizers, in general, provided higher grain production (ripe and total) and productivity. The combination of phosphate fertilizers and polymer-coated urea resulted in higher total production and grain yield in conilon coffee. In chapter 3, nitrogen fertilizers with associated technologies were efficient in increasing the productivity of conilon coffee in the three evaluated crops, when compared to conventional fertilizer, even in conditions of absence of irrigation.